Characterization of natural isolates of Lactobacillus strains to be used as starter cultures in dairy fermentation - Hebert, Elvira Maria (2000)
The technological relevant characteristics of five homofermentative lactobacilli strains, isolated from natural fermented hard cheeses, were studied. Isolates CRL 581 and CRL 654, from Argentinian artesanal hard cheeses, and isolates CRL 1177, CRL 1178, and CRL 1179, from Italian Grana cheeses, were identified as Lactobacillus delbrueckii subsp. lactis and Lactobacillus helveticus, respectively, by physiological and biochemical tests, SDS-PAGE of whole-cell proteins and sequencing of the variable (V1) region of the 16S ribosomal DNA. All strains showed high levels of β- galactosidase activity. However, proteolytic activity varied widely among isolates. Strains CRL 581, CRL 654, and CRL 1177 hydrolyzed α- and β- caseins and were able to coagulate reconstituted skim milk in less than 16 h at 42°C. According to the substrate specificity, these proteinases have a caseinolytic activity comparable to that of the P(III)-type of lactococcal proteinases. No strains produced inhibitor substances (bacteriocin) and all were insensitive to attack by 14 L. helveticus- and L. delbrueckii subsp. lactis-specific bacteriophages.